Overuse Injury of the Epiphyseal Primary Physis - Caine, Dennis; Patel, Vandan; Nguyen, Jie C. (Seminars in Musculoskeletal Radiology, 2024)
Year-round participation in youth sport that involves high levels of repetitive movement fosters an environment in which overuse injuries are likely to occur. Epiphyseal primary physeal stress injuries (PSIs), unique to skeletally immature athletes, are a particular concern, given their potential for growth disturbance. Initially observed in Little League baseball players, these injuries are now known to affect the long bones around the shoulder, elbow, wrist, hand, knee, ankle, and foot of skeletally immature athletes involved in a variety of sport activities.This article offers an epidemiological and radiologic perspective on the extent and distribution of epiphyseal PSIs in youth sport. We also review a novel framework for understanding the pathophysiologic mechanisms causing these injuries. This information is essential for the early identification of epiphyseal PSIs and devising preventive measures that can reduce a delayed diagnosis and long-term morbidity. Preventing and reducing injury to the epiphyseal growth plates is essential because impairment and dysfunction can result in lifelong morbidity and a risk of premature osteoarthritis.
Keywords: overuse injury; youth sport; imaging; stress injury; fracture